2021
DOI: 10.7717/peerj.11337
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of zebrafish after introduction of non-biodegradable polyelectrolyte microcapsules into the circulatory system

Abstract: Polyelectrolyte microcapsules are among the most promising carriers of various sensing substances for their application inside the bloodstream of vertebrates. The long-term effects of biodegradable microcapsules in mammals are relatively well studied, but this is not the case for non-biodegradable microcapsules, which may be even more generally applicable for physiological measurements. In the current study, we introduced non-biodegradable polyelectrolyte microcapsules coated with polyethylene glycol (PMs-PEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…We also showed the sensitivity of the developed sensors to metabolic acidosis in fish tissues provoked by increased environmental CO 2 during this period. Previously, we demonstrated that free polymeric microcapsules with polyethylene glycol coating are recognized by the immune system after hours and cause chronic inflammation for weeks [ 50 ]. Therefore, the obtained result demonstrates the increase in the operating time of implanted optical sensors based on polyacrylamide hydrogel up to days and confirms that amorphous PAAH delays the immune response of incorporated microparticles.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed the sensitivity of the developed sensors to metabolic acidosis in fish tissues provoked by increased environmental CO 2 during this period. Previously, we demonstrated that free polymeric microcapsules with polyethylene glycol coating are recognized by the immune system after hours and cause chronic inflammation for weeks [ 50 ]. Therefore, the obtained result demonstrates the increase in the operating time of implanted optical sensors based on polyacrylamide hydrogel up to days and confirms that amorphous PAAH delays the immune response of incorporated microparticles.…”
Section: Discussionmentioning
confidence: 99%
“…PEG has long been utilized to improve the biocompatibility profile of other encapsulating compounds such as alginate [ 39 , 40 ]. In fact, the practice continues today with the combination of PEG with other encapsulants to obtain the desired physical features such as durability while improving the biocompatibility [ 41 , 42 ]. Specific to islets, PEG has been used with laborious methods that assemble individual layers of streptavidin and biotin-PEG conjugates to coat single islets [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of calcium carbonate particles as templates has gained relevance. This requires the use of ethylene-diamine-tetracetic acid for ensuring the template dissolution [29,31]. It is worth mentioning that the preparation of PEMUCs using sacrificial colloidal particles as templates is not recommended for specific application because the obtained capsules can retain some toxic residues from the templates (dirty capsules), or solvent traces.…”
Section: Towards the Fabrication Of Hollow Capsules: Immersive Assembly On Colloidal Templatesmentioning
confidence: 99%
“…This requires introducing optically active components in the LbL shell, which is commonly achieved by embedding metal nanoparticles, playing a very important role in intracellular release [208], multi-substance delivery [209], or endosomal escape [210]. The mechanism of the laser light activation relies on the heating of the particles by light irradiation, which can induce the rupture of the shell or the modification of its permeability [31,211]. Thus, the use of near infrared radiation allows triggering the release of doxorubicin from multilayers formed with poly(Llysine), bovine serum albumin, and a thermoresponsive gelatin hydrogel in which gold nanoparticles were embedded [212].…”
Section: Physically Induced Releasementioning
confidence: 99%
See 1 more Smart Citation